The Impact Of Financial Distress, Audit Committee, And Firm Size On The Integrity Of Financial Statements - Kusuma Indawati Halim (Universitas Serang Raya, 2021)
This study aims to examine the impact of Financial Distress, Audit Committee, and Firm Size on The Integrity of Financial Statements. The integrity of financial statements can reflect the company's financial performance. The research sample obtained were based on purposive sampling technique, is including 32 consumer goods industry sectors firms listed in Indonesian Stock Exchange over the period of 2013-2017. Sources of research data are annual reports. Data analysis used descriptive statistics, classic assumption tests, estimation models, and panel data regression analysis. The panel data regressions analysis was the methodology employed for verifying the factors that may influence the integrity of financial statements. Based on the results of the Chow test and the Hausman test, the appropriate panel data regression model to be used for this study is the fixed effects model. This study provides empirical evidence that financial distress is negatively associated with the the integrity of financial statements, while audit committee and company size have positive effect on the the integrity of financial statements. Keywords: Financial Distress, Audit Committee, Firm Size, Integrity of Financial Statements.